Philosophy of Marriage as a Means of Family Building and Social Transformation - Alex Kusmardani; Usep Saepulloh; Nurrohman Nurrohman; Aah Tsamratul Fuadah; Abdulah Syafi'i (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The essence of marriage is a commitment with careful planning for prosperity in reviving the earth through good offspring in a beneficial marriage. This research is library research. The type of research used is qualitative research and the type of research is descriptive analytic research. The problem approach used is a philosophical, sociological, psychological, medical, juridical approach. The results of the study show that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a family, a happy and eternal household based on the Almighty God. The principles of marriage are, the principle of Muasharah bi al-Ma'ruf, the principle of choosing a partner, the principle of equality, problems in the family, economic problems, family and social interventions, the problem of differences in building a family